Acquired Error in using Antibiotic for Surgery Patients in Iraqi Hospitals - Y. Alhamdani, Fadya (Iraqi Journal of Pharmaceutical Sciences, 2017)
The use of antibiotics (AB) in surgery focused in either treating established infection or to prevent suspected post-operative infection. Inappropriate use of antibiotic for treatment of patients with common infections is a major problem worldwide, with great implications with regards to cost of treatment and development of resistance to the antimicrobial agent. Moreover, antibiotics may often be dispensed without a clear clinical indication. This study was conducted to estimate the medication errors in using antibiotic for surgery patients which may effect their wound healing. A 260 patients with clean-contaminated and contaminated surgery were included from two teaching hospitals, 160 patient from Medical city hospital and 100 from Al-kadhimiya hospital, 86% were female and 32% were male, their age range was 40 +/- 15. The study shows that there are medication errors related to different causes: firstly, medical team error which include the nurse (70.9%) and the physician which include 1) delay in patient follow up after operation(5.9%) , 2) changing the AB without doing culture and sensitivity test (48.8%), and incomplete prescription order(13.1%). second: ordering error which include: 1) the absent of original source of AB (44.5%), 2) Error in availability of the chosen AB (74.8%), and third: error related to the patient itself include 1) socioeconomic situation (14.5%), 2) educational state (54.3%), finally error related to increase cost in dispensing more than one AB needed (80.1%), although the healing was (63.6 %), delay in response (25%) and complicated wound infection (5%), significant results were arrange nurse error and poor drug availability. In conclusion: medication errors are still common problem in our hospitals, which are mostly related to medical team and the pharmacists should give more effort to avoid these errors. Key wards: Acquired error, Antibiotic, Surgery patients.